Fertilizer value of urine in pumpkin (Cucurbita maxima L.) cultivation - Pradhan, Surendra K.; Pitkänen, Susanna; Heinonen-Tanski, Helvi (Agricultural and Food Science, 2010)
The fertilizer value of human urine was compared with mineral fertilizer in pumpkin (Cucurbita maxima) cultivation at a dose of 113 kg N ha-1 with no-fertilization used as control. The growth of the vine was better in urine fertilized pumpkins than in mineral fertilized and non-fertilized pumpkins. Total fruit biomass was higher in mineral fertilized plants compared to urine fertilized and non-fertilized pumpkins. Urine fertilized pumpkins may have suffered from lower potassium or higher chloride, thus they produced fewer flowers and fruits. However, total fruit biomass and the number of fruits were slightly higher in urine fertilized plants than in their non-fertilized counterparts, i.e. 17.2 t ha-1 more pumpkin could be produced with urine fertilizer. The microbial hygiene quality as well as the contents of soluble sugars, protein and taste quality were similar in all treatments, but lower nitrate and higher chloride contents were recorded in urine fertilized pumpkins than other treatments. In conclusion, our study shows that the production rate of urine fertilized pumpkins was somewhat lower than mineral fertilized pumpkins but it was higher than non-fertilized pumpkins. The hygienic quality was equally good with all treatments.;